ALIH AKSARA DAN ALIH BAHASA TEKS SYAIR BIMBINGAN ROHANI JILID PERTAMA DISUSUN OLEH H. MANSYURUDDIN TUANKU BAGINDO - Desrin, Fransiska; Hasanuddin WS, Hasanuddin WS (Jurnal Bahasa dan Sastra, 2019)
Transliteration and translation of  syair bimbingan rohani text on the first chapter compiled by H. Mansyuruddin Tuanku Bagindo ". Essay. Indonesian Literature Study Program, Indonesian and Regional Language and Literature Department, Faculty of Language and Art, Padang State University.This study aims to: (a) present a description of the manuscript of syair bimbingan rohani, (b) present the form of transliteration from the Malay Arabic script to the Latin script of the Syair bimbingan rohani text, (c) present the form of translation from Malay-Minang to Indonesian syair bimbingan rohani text.This research is philology. The object of the research is the text of the Syair bimbingan rohani. The method used in this study is adjusted to the stages of research. In the data collection stage, that used field study methods. In the data processing stage, that used the descriptive. At the stage of transliteration used the transliteration method, and the translation used the translation method.The results of this study are (a) describing the text of the Syair bimbingan rohani, (b) the presentation of the script from the text of the Syair bimbingan rohani which can be read and understood by the society, (c) the presentation of the text of the Syair bimbingan rohani adapted to the Spelling of the Language Indonesia (EBI). This text reflects about how to educate the heart and soul to understanding that is  called Happy Life According to Islam, blessed by Allah, that starts from nurturing the tongue, leading the physical realm, guarding the eyes, keeping the ears, guarding the feet, how to keep an eye on the spiritual realm or the heart, and both parts, the second is  upbringing, the friend's question to the prophet, and the third part is upbringing. so, In the text of the Syair bimbingan rohani is found in the old Malay language and some Minangkabau language vocabulary which is maintained to protect  the purity of the old vocabulary.Keywords: Philology, scripture, transliteration, translation